Number of siblings and educational attainment: application of son preference. Issue 2 (19th January 2018) - Lin, Hung-Han
ABSTRACT: This article examines the relation between the number of children in Taiwanese families and the educational attainment of those children. To identify the causal relation, our analysis operationalizes the traditional Taiwanese parental preference for male children as an instrumental variable to generate exogenous variations in the number of siblings. Ordinary least square estimates reveal that a larger number of siblings results in lower educational attainment. However, after addressing for the endogeneity of the number of siblings, our two-stage least square estimates result in doubt of the existence of a trade-off between child quantity and quality within a family.